The impact of government actions and risk perception on the promotion of self-protective behaviors during the COVID-19 pandemic - Alvarez-Galvez, Javier; Anastasiou, Andreas; Lamnisos, Demetris; Constantinou, Marios; Nicolaou, Christiana; Papacostas, Savvas S.; Vasiliou, Vasilis S; McHugh, Louise; Lubenko, Jelena; Ruiz, Francisco J.; Paez-Blarrina, Marisa; Montesinos, Francisco; et al. (My University, 2023)
We aim to understand the factors that drive citizens of different countries to adhere to recommended self-protective behaviors during the COVID-19 pandemic.